Odontogenic Keratocyst finding with Cone Beam Computed Tomography (CBCT): a case report - Phimatra Jaya Putra; Hutomo Mandala Hartoyo; Mellisa Sim (Ikatan Radiologi Kedokteran Gigi Indonesia, 2021)
Objectives: The purpose of this case report is to analyze the incidental finding of an odontogenic keratocyst on cone beam computed tomography (CBCT) examination for the case of an impacted tooth 48. Case Report: A 48-year-old man came with a consul letter to perform a CBCT examination with complaints of loose teeth on the right posterior mandible starting from the premolars. Coincidentally found on a sagittal view showed a wide radiolucency lesion on the internal part of the jaw and not related to the impacted tooth. The treatment plan is to remove the lesion and perform a biopsy and perform postoperative panoramic radiograph. Conclusion: The characteristics of the odontogenic keratocyst lesion can be visualized clearly on CBCT. The use of CBCT in analyzing the type and size of the lesion is very helpful in planning surgical treatment. Odontogenic keratocysts can be well-diagnosed using a combination of CBCT examination with histopathological examination to determine the most effective management and prevent a recurrence.